Synthesis and Optical Properties of Novel Red-Emitting PbNb2O6: Eu3+ Phosphors - DEMİR, ABDULLAH; DEMİRER, HALİL; EKMEKÇİ, METE KAAN (SPRINGER/PLENUM PUBLISHERS, 2016)
Undoped and PbNb2O6:Eu3+ (1.0 aecurrency sign x aecurrency sign 6.0 mol%) phosphors were synthesized at 1100 A degrees C for 3.5 h by the conventional solid state reaction method. Synthesized PbNb2O6:Eu3+ phosphors were characterized by X-ray diffraction (XRD), Scanning electron microscopy (SEM), Energy dispersive spectroscopy (EDS) and Photoluminescence (PL) analyses. The PL spectra showed series of excitation peaks between 350 and 430 nm due to the 4f-4f transitions of Eu3+. For 395.0 nm excitation, emission spectra of Eu3+ doped samples were observed at 591 nm (orange) and 614 nm (red) due to the D-5(0) -> F-7(1) transitions and D-5(0) -> F-7(2) transitions, respectively. PL analysis results also showed that the emission intensity increased by increasing Eu3+ ion content. No concentration quenching effect was observed. The CIE chromaticity color coordinates (x,y) of the PbNb2O6:Eu3+ phosphors were found to be in the red region of the chromaticity diagram.
Keywords: PbNb2O6; XRD-SEM; Eu3+; Photoluminescence; Red LEDs; LEAD METANIOBATE; SOLID-SOLUTIONS; ENERGY-TRANSFER; QUANTUM DOTS; PIEZOELECTRIC PROPERTIES; BAND-GAP; PBS; PHOTOLUMINESCENCE; MICROSTRUCTURE; FABRICATION